Valoración significativa del componente bucal de la salud - Gonzalo Jaramillo-D; Catalina Botero-A; Angela María David; Sandra Bibiana Hincapie-C; Nubia Ximena Ramírez; Jaime Humberto Varela (Universidad de Antioquia, 2003)
The study of the social representation is a question of what is significant, because it gives the individual identity reasons, for the value that is granted to a fact, phenomenon or specific situation; parting from the clarification of such question, we can elucidate the scope that is given to the structure of thinking of the dental profession regarding the motivations that induce the community to significantly value or not, the oral component of its health and consequently the direction and performance of the dental profession. A qualitative study such as this one is oriented towards the comprehension or interpretation, from the observation and interview of the meaningful value that a social group gives to their health, specifically of the oral component; allowed us to identify group categories that speak of such meaningful valuation, allowing the desired comprehension enabling us to sustain and recreate new categories of analysis. The frame reference of the affirmation of the significance that the persons interviewed grant to their oral health is the family with its values and expectations catalyzed also by the context in which one lives, the educational organizations, the media and the health institutions. The strengthening of the personal identity is bound to the aesthetic, to the appraisal that one has of himself and to the one the others establish on their oral health. The comprehensive health is valued from oral health parting from functionality, the interdependence of the positive or negative experiences and again of the value granted by others. For the strengthening of the identity around oral health there is an association of the individual to his practices of self care arrived at from the different institutional spaces.